Infantile Hypertrophic Pyloric Stenosis at the Hospital Central P.N.P. Lima-Peru. A Ten Years Retrospective Survey - Orue Orue, Moncerrat (1999)
OBJECTIVE: To establish the incidence of Infantile Hypertrophic Pyloric Stenosis (IHPS) at Hospital de Policia, its associated factors and propose a procedure guideline for IHPS. MATERIAL AND METHODS: Retrospective study of patients who underwent IHPS surgical repair in the Hospital de Policía Pediatric Surgery Department between January 1985 and December 1994. RESULTS: We found 44 cases (incidence 1,67 x 1 000 live-born children), 35 (79%) were male, and the average age of initiation was 3rd to 4th week of life (range: 16-67 days). Predominant symptom was vomiting (100%). All of them underwent pyloromiotomy (Fredet-Ramstedt’s technique). 45% of patients complains postoperative complications, and vomiting (27%) was the most frequent one. There was no mortality. CONCLUSION: Our clinical and epidemiological features for IHPS were similar to those observed in other studies. Mean age 3 to 5 weeks, male gender, first child, and breastfeeding were the most associated factors.